Carole Landis : a most beautiful girl - Gans, Eric Lawrence, 1941- (Hollywood legends series., 2008)
Despite appearing in twenty-eight movies in little over a decade, Carole Landis (1919-1948) never quite became the major Hollywood star her onscreen presence should have afforded her. Although she acted in such enduring films as A Scandal in Paris and Moon over Miami, she was most often relegated to supporting roles. Even when she played the major role in a feature, as she did in The Powers Girl and the film noir I Wake Up Screaming!, she was billed second or third behind other actors. This biography traces Landis's life, chronicling her beginnings as a dance hall entertainer in San Francisc.